1995
DOI: 10.2307/4002252
|View full text |Cite
|
Sign up to set email alerts
|

Seed Size Distribution, Germination, and Emergence of 6 Switchgrass Cultivars

Abstract: Sdtchgrass (Punicum virgatum L.) has potential as a forage and biomass crop, but difficult establishment has limited its use. Germination and emergence were studied for 6 eultivars of suitchgrass ('Alamo', 'Blac~~ell', 'Cave-in-Rock', 'Kanlow', 'Pathfinder', and 'Trailblazer'). Germination studies Tvere conducted to determine the effect of light on germination and coleoFfile length, and to determine the effect of seed size (40,50, 63, 700, and SO" air valve settings for a South Dakota seed blower) an germinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 6 publications
5
56
1
3
Order By: Relevance
“…The cocultivated plants consistently produced higher levels of root biomass than control plants, suggesting a greater potential to sequester carbon and hold soils, both highly desired properties in a crop grown under low-input conditions. As with many warm-season perennial grasses, switchgrass can be difficult or slow to establish (1,20), and this is a major impediment to its implementation as a primary bioenergy crop (5). Therefore, both the shoot-and root-growth-promoting effects of S. vermifera, particularly at early points in plant development, are likely to improve competitiveness of switchgrass seedlings, especially during the establishment process.…”
Section: Vol 77 2011 Symbiosis Offsets Drought-related Biomass Lossmentioning
confidence: 99%
“…The cocultivated plants consistently produced higher levels of root biomass than control plants, suggesting a greater potential to sequester carbon and hold soils, both highly desired properties in a crop grown under low-input conditions. As with many warm-season perennial grasses, switchgrass can be difficult or slow to establish (1,20), and this is a major impediment to its implementation as a primary bioenergy crop (5). Therefore, both the shoot-and root-growth-promoting effects of S. vermifera, particularly at early points in plant development, are likely to improve competitiveness of switchgrass seedlings, especially during the establishment process.…”
Section: Vol 77 2011 Symbiosis Offsets Drought-related Biomass Lossmentioning
confidence: 99%
“…4 The seed size variation has been shown to have several important ecological implications. It may affect seed germination, 5 emergence, 6 seedling establishment, 7 growth rate and plant size, 8 survivorship, 9 competitive ability and reproductive ability of adult plant. 10 Several studies carried out on weeds and crops have revealed that seedling size is usually directly related with food reserves and energy content of seeds which increases with seed weight.…”
Section: Introductionmentioning
confidence: 99%
“…In both 1995 and 1996, weight of seeds became significantly heavier for seeds collected later in the growing season (Table 2). Heavier seeds within a seed lot have been shown to exhibit higher germination amounts and better seedling emergence characteristics than lighter seeds (Aiken and Springer 1995, Limbach and Call 1996, Hou and Romo 1998. Seeds collected later in the process of seed head maturation also exhibit greater seed germination amounts (Phaneendranath et al 1978).…”
Section: Resultsmentioning
confidence: 99%